The Best Village Selection Decision Support System in Simalungun Regency Using the SAW Method - Ina Kusanti Purba; Rahmat Widia Sembiring; Saifullah Saifullah (Yayasan Literasi Sains Indonesia, 2023)
This study aims to develop a decision support system to select the best village in Simalungun District. The SAW (Simple Additive Weighting) method is used for decision-making. This system is designed to assist local governments and related stakeholders in selecting the best villages based on relevant criteria. The criteria covered aspects such as community education, public health, community economy, security and order, community participation, governance, social institutions, and family empowerment and welfare. Consideration of each criterion's weight or level of importance is carried out by involving experts and relevant stakeholders. The SAW method calculates the performance scores of existing villages based on predetermined criteria. The score is then used in the ranking process to determine the best village. Based on the research results, alternative villages that deserve the title of the best village are Marubun Bayu village as rank 1, Dolok Maraja as rank 2 and Naga Jaya II as rank 3. This research is expected to provide significant benefits for decision-makers in selecting the best village in Simalungun Regency to increase efficiency and objectivity in the decision-making process, as well as encourage more sustainable and equitable development in all the villages of Simalungun Regency.